(untitled) (The Pretoria Student Law Review, 2021)
Climate change is a threat to the earth and sustainable development. There is no country in the world that is not experiencing first-hand, the drastic effects of climate change.7 Indeed, a large section of the global population already suffers or is in some way affected by the adverse effects of climate change, including its impacts on agriculture, aquaculture, livelihoods, biological diversity, health and a broad range of human rights. Although the impacts of climate change are felt globally, developing countries will bear the brunt of their social, economic and environmental effects.